2016
DOI: 10.1016/j.ijsolstr.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Time domain finite element estimates of dynamic stiffness of viscoelastic composites with stiff spherical inclusions

Abstract: a b s t r a c tA weighted residual time domain unstructured mesh finite element approach was used to obtain numerical estimates for the dynamic stiffness of medium and high stiffness contrast composites consisting of viscoelastic epoxy matrix filled with stiff spherical inclusions. Both random and regular microstructure composites were studied. It was shown that over the broad temperature and inclusion fraction ranges studied, the generalized self-consistent model ( Christensen and Lo, 1979 ) provided accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…The material parameters are given in Table 1 the GSC scheme provides accurate estimates. These results are consistent with the ones obtained in [25] by using finite-element computations with a time-integration approach. It can be also noted that the SC scheme, which presents a percolation threshold for an infinite mechanical contrast, leads to an unrealistic quasi-elastic effective response at volume fraction c = 0.5.…”
Section: Assessment Of Mean-field Models With Respect To Fft Referencsupporting
confidence: 92%
See 2 more Smart Citations
“…The material parameters are given in Table 1 the GSC scheme provides accurate estimates. These results are consistent with the ones obtained in [25] by using finite-element computations with a time-integration approach. It can be also noted that the SC scheme, which presents a percolation threshold for an infinite mechanical contrast, leads to an unrealistic quasi-elastic effective response at volume fraction c = 0.5.…”
Section: Assessment Of Mean-field Models With Respect To Fft Referencsupporting
confidence: 92%
“…with q k = 1 + 2(ωτ k ) α cos πα 2 + (ωτ k ) 2α . From the approximation (33) and the conditions on time integrals of the effective relaxation spectrum (25), it follows that…”
Section: Approximation Of the Effective Relaxation Spectrum Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions are in good agreement with the limits postulated before, so we can claim homogeneity of the RVEs containing parallel pores. Note that the isotropy of a structure can also be evaluated when the effective properties are known, see for example, and Gusev (2016b) .…”
Section: Characterization Of the Generated Microstructures: Homogeneimentioning
confidence: 99%
“…Recently, Gusev presented time-domain finite element simulation for composites with different microstructures, including composites with viscoelastic coated spherical inclusions. It was found that the n-layered model [8] is remarkably accurate even in the case of high stiffness contrast and thin coating layers [12][13][14]. Unwin et al further highlighted the progress in damping techniques by the use of polymer composites with viscoelastic coated spherical inclusions [15,16].…”
Section: Introductionmentioning
confidence: 99%